Perencanaan Proses Pengolahan Sampah Plastik dan Kebun di Kabupaten Boyolali dengan Prinsip Karbonisasi Menjadi Energi - Rini, Mayang Ananda; Sari, Novica Ayu; Oktaviani, Whindy Ndaru; Ghaida, Rarastika Nur; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Jurnal Energi Dan Manufaktur, 2022)
Waste management in Boyolali Regency is one of the challenges to achieve the smart city criteria. Garbage in Bolali Regency contains 56.12% plastic composition and 37.13% garden waste. Plastic and garden waste has a calorific value that exceeds 5000 kcal/kg, so it can be used as briquettes. The purpose of this study is to analyze the proper planning and can be carried out in Boyolali Regency by using the carbonization process to produce quality briquettes. The waste processing process consists of the process of sorting plastic waste and garden waste, then counting, then carbonization is carried out, so that briquettes are obtained according to standards. The total waste treated is about 90 ton/day and 45 ton/day, for plastic waste and garden waste respectively. If this process is applied at least, it can reduce as much as 50.77% of waste generation in Boyolali Regency. The total recovery of waste energy from the carbonization facility can reach 5611384.6 MJ/day. The land requirement from the processing process reaches 117 ² with the layouting process having dimensions of 264 m x 65 m.